ASSOCIATION BETWEEN ADHERENCE TO HYPERTENSION MEDICATION AND SELF-MANAGEMENT AMONG HYPERTENSION PATIENTS IN PUSKESMAS MAGELANG TENGAH MAGELANG: A CROSS-SECTIONAL SURVEY - PURBORINI, NURUL; KARTIKAWATI, NURFINA D.; HIDAYAH, NURUL; ARUMI, ENDAH R.; YULIASTUTI, FITRIANA (International Journal of Applied Pharmaceutics, 2025)
Hypertension, a leading global health concern, is particularly prevalent among the older adult population. It is defined as persistently elevated arterial blood pressure, with readings of 140/90 mmHg or higher. This study was investigated whether adherence to hypertension medication is associated with self-management among patients with hypertension in Puskesmas Magelang Tengah, Magelang, who participated in the Program Pengelolaan Penyakit Kronis (Prolanis) and Program Rujuk Balik (PRB) Programs. We undertook a cross-sectional study by using questionnaires to explore demographic characteristics, adherence to hypertension medication (Morisky Green Levine Medication Adherence Scale/MGLS), and self-management (Persian Hypertension Self-Management Questionnaire/PHSMQ). The Spearman’s Rank test was used to investigate the association between adherence to hypertension medication and self-management among hypertension patients. Most participants were at an intermediate level of adherence to hypertension medication (47.2%) and had low self-management of Hypertension medication (60.4%). Based on Spearman’s Rank test, there was no significant association between adherence to hypertension medication and self-management among hypertension patients. Future research should investigate the role of other factors related to self-management in patients with hypertension, such as health literacy, motivation, and social support. These factors could provide deeper insights into how adherence and other components of self-management interact with one another.